Long-term prognosis of left ventricular re-remodeling after surgery of ischemic cardiomyopathy: the potential of tomographic radionuclide ventriculography - V. V. Shipulin; A. I. Mishkina; M. O. Gulya; Yu. V. Varlamova; S. L. Andreev; A. S. Pryakhin; V. M. Shipulin; K. V. Zavadovsky (Российский кардиологический журнал, 2020)
Aim. To assess the potential of stress tomographic radionuclide ventriculography (T-RVG) in long-term prognosis of left ventricular (LV) re-remodeling after surgery of ischemic cardiomyopathy.Material and methods. Thirty patients with ischemic cardiomyopathy, before surgical treatment, underwent resting T-RVG and with increasing doses of dopamine (5/10/15 pg/kg/min (5 min/dose). All patients underwent two-dimensional echocardiography before surgery, in the short- (7-14 days) and long-term postoperative period. In the long-term postoperative period (476±36 days), the patients were divided into two groups: group 1 (n=19) — patients with ongoing LV remodeling (increase in the LV end-systolic volume (ESV) or decrease <10% relatively short-term postoperative period), group 2 (n=11) — patients with decreased LV ESV >10%.Results. The results revealed significant differences between the groups in the dynamics (Δ) of the LV ejection fraction (EF) (%) (2 (2;8); 11 (5;12), p=0,02), peak ejection rate (%) (32 (14;51); 63 (34;79), p=0,009), LV dyssynchrony (PSDo (3 (0;7); -2 (-9;3), p=0,004); Entropy (%) (2 (-1;6); 0 (-4;2), p=0,01)). Univariate regression showed that ΔLVEF (odds ratio (OR), 0,88; confidence interval (CI), 0,8; 0,97; p=0.008), ΔLVPSD (OR, 1,13; CI, 1,03; 1,25; p=0,005), and coronary stenosis >75% (OR, 4,25; CI, 1,57; 11,48; p=0,001) had a predictive value. According to the ROC-analysis, the sensitivity, specificity, and AUC were 87%, 64% and 0,727 for ΔLVPSD (threshold >-1); 84%, 46% and 0,691 for coronary stenosis >75% >75% (threshold >2); 65%, 82% and 0,674 for ΔLVEF (threshold ≤4), respectively. The logistic model, which included these parameters and the presence of diabetes, showed a significantly greater AUC (0,907, p<0,05) compared with these indicators taken separately.Conclusion. Preoperative values of ΔLVEF and ΔLVPSD obtained with stress T-RVG have prognostic significance in relation to LV long-term re-remodeling.